"Practice What You Teach" Public Health Nurses Promoting Healthy Lifestyles (PHeeL-PHiNe): Program Evaluation. Issue 3 (July 2018) - Hasson, Ronnie; Stark, Aliza H.; Constantini, Naama; Polak, Rani; Verbov, Gina; Edelstein, Naomi; Lachmi, Michel; Cohen, Rivka; Maoz, Shuli; Daoud, Nihaya; Soltz-Aharony, Hannah; Stein-Zamir, Chen
Abstract : Healthy lifestyle programs are essential for meeting the challenge of noncommunicable diseases. The Public Health Nurses Promoting Healthy Lifestyles (PHeeL-PHiNe) program engaged nurses from family health clinics in Jerusalem District and included physical activity, healthy nutrition, and motivational skills. Questionnaires were completed at baseline, postintervention, and at 18 months. Results showed a marked effect on health practices. The proportion of nurses consuming a balanced diet and the use of food labels significantly increased and were maintained over time. Short-term improvements in physical activity were also observed. Nurses who practiced a healthy lifestyle were significantly more likely to provide guidance and counseling to families on healthy behaviors.